2019
DOI: 10.1080/16549716.2018.1556572
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition-specific and sensitive drivers of poor child nutrition in Kilte Awlaelo-Health and Demographic Surveillance Site, Tigray, Northern Ethiopia: implications for public health nutrition in resource-poor settings

Abstract: Background: Child undernutrition is a prevalent health problem and poses various short and long-term consequences.Objective: This study seeks to investigate the burden of child undernutrition and its drivers in Kilte Awlaelo-Health and Demographic Surveillance Site, Tigray, northern Ethiopia.Methods: In 2015, cross-sectional data were collected from 1,525 children aged 6–23 months. Maternal and child nutritional status was assessed using the mid upper arm circumference. Child’s dietary diversity score was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
2
4
0
Order By: Relevance
“…According to our study findings, 35.8% boys below 2 years were stunted where as the number was 31% for girls. Prevalence of wasting followed the similar path of higher wasting rate among boys compared to girls which is consistent with the previous studies from Pakistan, Ghana, and sub Saharan Africa ( Hazarika, 2010 ; Hong, 2007 ; Wamani et al., 2007 ; Abera et al., 2019 ). The possible reason behind girls' lower stunting and wasting rate than boys can be explained by some factors.…”
Section: Discussionsupporting
confidence: 90%
“…According to our study findings, 35.8% boys below 2 years were stunted where as the number was 31% for girls. Prevalence of wasting followed the similar path of higher wasting rate among boys compared to girls which is consistent with the previous studies from Pakistan, Ghana, and sub Saharan Africa ( Hazarika, 2010 ; Hong, 2007 ; Wamani et al., 2007 ; Abera et al., 2019 ). The possible reason behind girls' lower stunting and wasting rate than boys can be explained by some factors.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with the results reported by Santi et al (2012) in South Bengkulu that the higher the family income level is, the better the children's nutritional status will be (Santi et al, 2012). Several studies in other parts of Indonesia and abroad showed similar results of the relationship between poverty and malnutrition (Saputra et al, 2012;Suarni et al, 2016;Indarti, 2016;Chirwa et al, 2008;Busse et al, 2018;Abera et al, 2019). For example, studies in Malawi and Ethiopia report something similar to our results that children who come from economically capable households, in this case those having jobs or earning a living, tend to be more nutritious (Chirwa et al, 2008;Busse et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…In a second step, in case of related variables the most relevant one was selected on the basis of statistical significance and informational content provided. To enter the multivariable logistic regression a p-value of <0.25 in the bivariate analysis was the overarching criteria [28][29][30]. Merely the maternal educational level, well-recognized as a nutrition-sensitive indicator, was included independently of its significance level in the logistic regression model with a forward stepwise approach.…”
Section: Predictor Analysismentioning
confidence: 99%